Clinical and Financial Implications of 2 Treatment Strategies for Donor-derived Hepatitis C Infections. Issue 10 (7th September 2021) - Stewart, Zoe A.; Stern, Jeffrey; Ali, Nicole M.; Kalia, Harmit S.; Khalil, Karen; Jonchhe, Srijana; Weldon, Elaina P.; Dieter, Rebecca A.; Lewis, Tyler C.; Funches, Nur; Crosby, Sudara; Seow, Monique; et al.
Abstract : Background: Transplanting hepatitis C viremic donor organs into hepatitis C virus (HCV)-negative recipients is becoming increasingly common; however, practices for posttransplant direct-acting antiviral (DAA) treatment vary widely. Protracted insurance authorization processes for DAA therapy often lead to treatment delays. Methods: At our institution, 2 strategies for providing DAA therapy to HCV – recipients of HCV + transplants have been used. For thoracic organ recipients, an institution-subsidized course of initial therapy was provided to ensure an early treatment initiation date. For abdominal organ recipients, insurance approval for DAA coverage was sought once viremia developed, and treatment was initiated only once the insurance-authorized supply of drug was received. To evaluate the clinical impact of these 2 strategies, we retrospectively collected data pertaining to the timing of DAA initiation, duration of recipient viremia, and monetary costs incurred by patients and the institution for patients managed under these 2 DAA coverage strategies. Results: One hundred fifty-two transplants were performed using HCV viremic donor organs. Eighty-nine patients received DAA treatment without subsidy, and 62 received DAA treatment with subsidy. One patient who never developed viremia posttransplant received no treatment. Subsidizing the initial course enabled earlier treatment initiation (median, 4 d [interquartile range (IQR), 2–7] vs 10 [IQR, 8–13]; P < 0.001) and shorter duration of viremia (median, 16 d [IQR, 12–29] vs 36 [IQR, 30–47]; P < 0.001). Institutional costs averaged 9173 per subsidized patient and 168 per nonsubsidized patient. Three needlestick exposures occurred in caregivers of viremic patients. Conclusions: Recipients and their caregivers stand to benefit from earlier DAA treatment initiation; however, institutional costs to subsidize DAA therapy before insurance authorization are substantial. Insurance authorization processes for DAAs should be revised to accommodate this unique patient group.